Residue depletion of ivermectin in broiler poultry - Mestorino, Olga Nora (2017)
Helminth infections are widespread in the poultry industry. There is evidence of extra-label use of some drugs, such as ivermectin (IVM), in broiler poultry. Pharmacokinetic and residual studies of IVM in poultry, however, are rather scarce. Our aim was to determine time restrictions for broiler chickens fed with balanced feed mixed with IVM for 21 days, and thus achieve acceptable residual levels for consumption as established by the European Union. Sixty 1-day-old chicks were fed with food supplemented with IVM at 5 mg kg?1 feed for 21 days. Groups of six treated animals were sacrificed at 0, 1, 2, 4, 8, 10, 15, 20 and 28 days after treatment. Liver, skin/fat, kidney and muscle samples were obtained. IVM were determined by liquid chromatography with fluorescence detection after automatic solid-phase extraction with SPE C18 cartridges. The highest concentrations were measured in the liver, which is logical given that IVM is a drug that undergoes extensive hepatic metabolism. The optimal withdrawal time for edible tissues of these animals to stay within the permitted residual levels were: 12 days for liver, 8 days for skin/fat, 0 days for muscle and 10 days for kidney.